2020
DOI: 10.1136/bmjopen-2019-031708
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding adjunctive hyperbaric oxygen therapy to standard wound care for diabetic foot ulcers: a protocol for a systematic review with meta-analysis and trial sequential analysis

Abstract: IntroductionDiabetic foot ulcer represents a major health problem globally. Preliminary studies have indicated that systemic treatment of diabetic foot ulcer patients with hyperbaric oxygen therapy have beneficial effects on wound healing, risk of amputation, glycaemic control, atherosclerosis, inflammatory markers and other clinical and laboratory parameters. This protocol for a systematic review aims at identifying the beneficial and harmful effects of adding hyperbaric oxygen therapy to standard wound care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 105 publications
0
13
0
1
Order By: Relevance
“…Compared to other commonly employed techniques such as ankle brachial index, TCOM and so on, PA imaging is the best predictor for wound healing (AUC = 0.915, Table 2). PA classification could allow wound specialists to change their course of treatment if the wound is not responding to conventional treatment protocols 15,25,53,54 . This would in turn improve outcomes, reduce amputations, healing time and costs.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other commonly employed techniques such as ankle brachial index, TCOM and so on, PA imaging is the best predictor for wound healing (AUC = 0.915, Table 2). PA classification could allow wound specialists to change their course of treatment if the wound is not responding to conventional treatment protocols 15,25,53,54 . This would in turn improve outcomes, reduce amputations, healing time and costs.…”
Section: Discussionmentioning
confidence: 99%
“…The infection of large bone defects filled with bone substitute after enucleation is still a serious issue in the treatment of large cysts [13]. Therefore, a new and effective treatment method is much needed, and HBOT has been suggested as a promising solution [17][18][19]. Therefore, we conducted a randomized controlled clinical trial to assess the effects of HBOT during the treatment of patients whose bone defects were filled with bone substitute after enucleation.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperbaric oxygen therapy (HBOT) is a kind of treatment whereby patients inhale 100% oxygen at super-atmospheric pressure and has been widely used in refractory diseases, osteomyelitis, compromised skin graft and flap, anaerobic and so on 17 . There are many studies that showed that HBOT could inhibit the growth of anaerobic bacteria, ease inflammation, and promote ossification 18 , 19 . Therefore, we propose that HBOT could help to reduce the risk of postoperative complications, as well as promoting ossification after enucleation.…”
Section: Introductionmentioning
confidence: 99%
“…It can also have therapeutic importance in wounds from burns and diabetic ulcers. 34 35 36 It has a positive role in compromised flaps and can increase the effective size of composite graft survival, and improve prognosis of flap survival. Generally the skin grafts contain different tissue types with varying sizes that lack proper blood supply and are depended on the host for nutrient.…”
Section: Linical Application As T Herapeutic U Ses Of H Yperbaric O mentioning
confidence: 99%